Multidimensional poverty and COVID-19 risk factors: A rapid overview of interlinked deprivations across 5.7 billion people - Alkire, S; Dirksen, J; Nogales, R; Oldiges, C (Oxford Poverty and Human Development Initiative (OPHI), 2020)
Multidimensional poverty data and measurement are key allies in confronting the threat posed by the COVID-19 pandemic. Formulating an effective response to this global crisis requires an understanding of the overlapping deprivations faced by people in the developing world, deprivations that can result in increased vulnerability to COVID-19. The global Multidimensional Poverty Index (MPI) provides clear, immediate evidence of these interlinked deprivations, making interventions more effective, high impact, and durable.